Effect of immune checkpoint inhibitor therapy on biventricular mechanics in cancer patients over a short-term follow-up: a systematic review - Sonaglioni, Andrea; Bruno, Antonino; Nicolosi, Gian Luigi; Fossile, Emanuela; Rubuano, Cristian; Ricotta, Riccardo; Gemelli, Maria; Lombardo, Michele; Muti, Paola; Bassani, Barbara (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICI) have demonstrated a survival benefit in various cancer types. A few numbers of imaging studies have recently measured myocardial strain parameters in cancer patients before and after ICI treatment, reporting not univocal results. This systematic review has been primarily designed to summarize the main findings of these studies and to examine the overall effect of ICI therapy on biventricular mechanics in cancer patients.MethodsAll imaging studies evaluating the effect of ICI therapy on biventricular mechanics in cancer patients, selected from PubMed and EMBASE databases, were included. Imaging studies that analyzed myocardial strain parameters in highly selected cancer patients with ICI-related myocarditis were excluded. Relative change (RC) (%) from baseline of conventional and innovative indices of biventricular function was determined. Prevalence of cardiovascular complications was also assessed.ResultsThe full-texts of 12 studies with 554 ICI-treated cancer patients were analyzed. Myocardial strain parameters were measured by two-dimensional-speckle tracking echocardiography (STE) in seven studies, three-dimensional STE in two studies and cardiac magnetic resonance feature tracking in the remaining three studies. Average duration of follow-up was 3.1 months (range 0.5-7.3 months). All conventional indices of biventricular mechanics showed small and not statistically significant change after ICI treatment (RC ranging between -6.9 and +4.8%). Conversely, average left ventricular (LV)-global longitudinal strain (GLS), LV-global circumferential strain, LV-global radial strain, left atrial reservoir strain, right ventricular (RV)-GLS, RV-free wall longitudinal strain and right atrial reservoir strain were significantly worsened after ICI treatment (RC ranging between -9 and -19.2%). A definite cancer therapy-related cardiac dysfunction (CTRCD) was detected in 28.3% of ICI-treated patients (range 19.4-38.1%). The pooled prevalence of acute ICI-related myocarditis was 0.8% (range 0-4.6%) over follow-up period. Three out of seven ICI-related myocarditis patients (42.8%) were diagnosed with fulminant acute myocarditis.ConclusionsICI treatment causes a significant deterioration of biventricular mechanics, early diagnosed by strain imaging methods. Myocardial strain parameters are more sensitive than conventional indices of systolic function for the early detection of subclinical ICI-related cardiotoxicity.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier INPLASY202490131.